2019
DOI: 10.1371/journal.pone.0210064
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of probiotic/colostrum supplementation on gut function in children with autism and gastrointestinal symptoms

Abstract: Over half of all children with autism spectrum disorders (ASD) have gastrointestinal (GI) co-morbidities including chronic constipation, diarrhea, and irritable bowel syndrome. The severity of these symptoms has been correlated with the degree of GI microbial dysbiosis. The study objective was to assess tolerability of a probiotic (Bifidobacterium infantis) in combination with a bovine colostrum product (BCP) as a source of prebiotic oligosaccharides and to evaluate GI, microbiome and immune factors in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
135
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 97 publications
6
135
1
11
Order By: Relevance
“…To date only few studies explored the effects of probiotics on ASD clinical features in humans. Table 1 synthesizes available evidence on the efficacy and safety of probiotic supplementation as an adjunctive treatment for ASD [49,51,73,[95][96][97][98][99][100][101][102][103][104][105][106]. In these studies, probiotic interventions varied across all of the trials.…”
Section: Probioticsmentioning
confidence: 99%
See 4 more Smart Citations
“…To date only few studies explored the effects of probiotics on ASD clinical features in humans. Table 1 synthesizes available evidence on the efficacy and safety of probiotic supplementation as an adjunctive treatment for ASD [49,51,73,[95][96][97][98][99][100][101][102][103][104][105][106]. In these studies, probiotic interventions varied across all of the trials.…”
Section: Probioticsmentioning
confidence: 99%
“…Additionally, in the same study, the efficacy of probiotic supplementation seemed to be age-dependent, with better effects noticed on younger children, underscoring the importance of early interventions. Although all aforementioned studies showed changes in GM after the implementation diet with probiotics, only some of them analyzed the correlations with GI symptoms and reported improvement of GI function indices [96,98,101,102,105]. In fact, a survey conducted on caregivers showed that daily administration of a specific five-strain probiotic decreased the severity of comorbid GI problems [99].…”
Section: Probioticsmentioning
confidence: 99%
See 3 more Smart Citations